Kendala Penilaian Aspek Keterampilan (KI-4) Membaca Surat Al-Maidah Ayat 2-3 di Kelas VI SDN 2 Bantarwuni Selama Masa Pandemi Covid-19 - Halili, Halili; Hasanah, Nur Ziadatul (Lembaga Rumah Indonesia, 2021)
Covid-19 has many negative effects on education. The government took an emergency policy in the form of school from home. Because of this policy, online teaching and learning activities are carried out from home. However, the reality in the field, such as what happened in SDN 2 Bantarwuni, there are several obstacles such as what happened in the psychomotor domain assessment process in reading surah al-Maidah verses 2-3. This study aims to: (1) Understand how the psychomotor domain assessment process in reading al-Maidah verse 2-3 at SDN 2 Bantarwuni; (2) Understand the conditions and constraints faced in the assessment of the psychomotor domain in reading al-Maidah verses 2-3 at SDN 2 Bantarwuni. This research is a qualitative field research. The method of data collection was done by observation at SDN 2 Bantarwuni and documentation. The results of this study: (1) The assessment process was carried out according to the procedure, except that there were some students who did not submit the assessment assignment; (2) The obstacles faced are the lack of effort from students and parents to collect assignments via the WhatsApp application or directly carry out face-to-face assessments at school.